Lifetime hypertension as a predictor of brain structure in older adults: cohort study with a 28-year follow up. - Allan, C; Zsoldos, E; Filippini, N; Sexton, C; Topiwala, A; Valkanova, V; Singh-Manoux, A; Tabák, A; Shipley, M; Mackay, C; Ebmeier, K; Kivimäki, M (2014)
Background Hypertension is associated with an increased risk of dementia and depression with uncertain longitudinal associations with brain structure. Aims To examine lifetime blood pressure as a predictor of brain structure in old age. Method A total of 190 participants (mean age 69.3 years) from the Whitehall II study were screened for hypertension six times (1985-2013). In 2012-2013, participants had a 3T-magnetic resonance imaging (MRI) brain scan. Data from the MRI were analysed using automated and visual measures of global atrophy, hippocampal atrophy and white matter hyperintensities. Results Longitudinally, higher mean arterial pressure predicted increased automated white matter hyperintensities (P < 0.002). Cross-sectionally, hypertensive participants had increased automated white matter hyperintensities and visually rated deep white matter hyperintensities. There was no significant association with global or hippocampal atrophy. Conclusions Long-term exposure to high blood pressure predicts hyperintensities, particularly in deep white matter. The greatest changes are seen in those with severe forms of hypertension, suggesting a dose-response pattern.